The Association Between Differing Grip Strength Measures and Mortality and Cerebrovascular Event in Older Adults: National Health and Aging Trends Study - Whitney, Daniel G.; Peterson, Mark D. (Frontiers in Physiology, 2019)
The purpose of this study was to compare the predictive capacity of different post-processing methods of hand grip strength (GS) for mortality and incident cerebrovascular events in older adults. A sample of 4,143 participants aged 65 years and older was included from the National Health and Aging Trends Study (NHATS) and followed for 6 years. GS measures included baseline (i.e., round 1) (1) absolute GS, (2) GS divided by body mass (NGSmass), and (3) GS divided by body mass index (NGSBMI), as well as (4) change in absolute GS from round 1 to round 2 (GS1-2). Cox proportional hazards regression models were used to examine the association between sex- and age group-specific tertiles of GS measures (weak, moderate-strength, strong) with mortality (n=641) and incident cerebrovascular events (n=329). Absolute GS (hazard ratio [HR]=1.83; 95% confidence interval [CI]=1.51-2.22), NGSmass (HR=1.46; 95% CI=1.21-1.76), and NGSBMI (HR=1.50; 95% CI=1.24-1.82) were each associated with mortality among weak participants, but not GS1-2 (HR=1.10; 95% CI=0.99-1.46). NGSmass (HR=1.54; 95% CI=1.19-2.01) and NGSBMI (HR=1.37; 95% CI=1.06-1.79) were both associated with incident cerebrovascular event among weak participants, but not absolute GS (HR=1.12; 95% CI=0.86-1.47) or GS1-2 (HR=1.11; 95% CI=0.85-1.44). Absolute GS, NGSmass, and NGSBMI were each associated with mortality, whereas only NGSmass and NGSBMI were associated with cerebrovascular event. These findings suggest that different post-processing methods of GS may have differing predictive capacity in the elderly depending on the outcome of interest; however, since NGS measures were associated with both mortality and cerebrovascular events, they may be considered advantageous for screening in older adults.